Macroeconomic and industry effects of supply-side climate policy: Dutch disease in reverse? - Ådne Cappelen; Marek Jasinski; Håvard Hungnes; Julia Skretting (Statistics Norway, Research Department, 2024)
Petroleum-producing countries face unique challenges in meeting global emissions targets. As global petroleum consumption declines, these nations must reallocate resources and phase out a historically profitable industry. This study examines Norway's economic transformation resulting from a significant downturn in the petroleum sector, akin to a reverse Dutch disease. Industries linked to petroleum, particularly those supplying factor inputs, must pivot to new markets, while other sectors may benefit from real exchange rate depreciation. Our findings indicate that long-term macroeconomic adjustments are modest, whereas short-term effects can be significant but are largely mitigated through standard fiscal and monetary policy measures.
Keywords: Q32; Q54; E60; F41; 330; Petroleum industry; Green transition; Dutch disease